Ten years of feasibility pump, and counting - Berthold, Timo; Lodi, Andrea; Salvagnin, Domenico (EURO journal on computational optimization, 2019)
The Feasibility Pump (fp) is probably the best-known primal heuristic for mixed-integer programming. The original work by Fischetti et al. (Math Program 104(1):91–104, 2005), which introduced the heuristic for 0–1 mixed-integer linear programs, has been succeeded by more than twenty follow-up publications which improve the performance of the fp and extend it to other problem classes. Year 2015 was the tenth anniversary of the first fp publication. The present paper provides an overview of the diverse Feasibility Pump literature that has been presented over the last decade.